Representation of Interpersonal Communication Patterns in the Podcast by Deddy Corbuzier “Log In episode 15” - Mochammad Robi Ardiansyah Supiatun; Sufyanto Sufyanto (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative research aims to analyze the interpersonal communication patterns in Deddy Corbuzier's podcast, specifically focusing on